PL02: A randomized, controlled comparison of electrical versus pharmacological cardioversion for emergency department patients with recent-onset atrial fibrillation. (May 2019) - Stiell, I.; Perry, J.; Birnie, D.; Macle, L.; Vadeboncoeur, A.; Thiruganasambandamoorthy, V.; Borgundvaag, B.; Brison, R.; Hohl, C.; McRae, A.; Rowe, B.; Sivilotti, M.; et al.
Abstract : Introduction : For rhythm control of acute atrial fibrillation (AAF) in the emergency department (ED), choices include initial drug therapy or initial electrical cardioversion (ECV). We compared the strategies of pharmacological cardioversion followed by ECV if necessary (Drug-Shock), and ECV alone (Shock Only).Methods : We conducted a randomized, blinded, placebo-controlled trial (1:1 allocation) comparing two rhythm control strategies at 11 academic EDs. We included stable adult patients with AAF, where onset of symptoms was <48 hours. Patients underwent central web-based randomization stratified by site. The Drug-Shock group received an infusion of procainamide (15mg/kg over 30 minutes) followed 30 minutes later, if necessary, by ECV at 200 joules x 3 shocks. The Shock Only group received an infusion of saline followed, if necessary, by ECV x 3 shocks. The primary outcome was conversion to sinus rhythm for ≥30 minutes at any time following onset of infusion. Patients were followed for 14 days. The primary outcome was evaluated on an apriori-specified modified intention-to-treat (MITT) basis excluding patients who never received the study infusion (e.g. spontaneous conversion). Data were analyzed using chi-squared tests and logistic regression. Our target sample size was 374 evaluable patients.Results : Of 395 randomized patients, 18 were excluded from the MITT analysis; none were lost to follow-up. The Drug-Shock (N = 198) and Shock Only (N = 180) groups (total = 378) were similar for all characteristics including mean age (60.0 vs 59.5 yrs), duration of AAF (10.1 vs 10.8 hrs), previous AF (67.2% vs 68.3%), median CHADS2 score (0 vs 0), and mean initial heart rate (119.9 vs 118.0 bpm). More patients converted to normal sinus rhythm in the Drug-Shock group (97.0% vs 92.2%; absolute difference 4.8%, 95% CI 0.2-9.9; P = 0.04). The multivariable analyses confirmed the Drug-Shock strategy superiority (P = 0.04). There were no statistically significant differences for time to conversion (91.4 vs 85.4 minutes), total ED length of stay (7.1 vs 7.7 hours), disposition home (97.0% vs 96.1%), and stroke within 14 days (0 vs 0). Premature discontinuation of infusion was more common in the Drug-Shock group (8.1% vs 0.6%) but there were no serious adverse events.Conclusion : Both the Drug-Shock and Shock Only strategies were highly effective and safe in allowing AAF patients to go home in sinus rhythm. A strategy of initial cardioversion with procainamide was superior to a strategy of immediate ECV.